A daughter's frustration with the dearth of patient- and family-centered care - Cindy Brach (The Beryl Institute, 2014)
Patient involvement in decision-making is an increasingly recognized ethical imperative, one that requires attention to health literacy. Health care that is truly patient- and family-centered, however, is the exception rather than the rule. This first person account of a hospitalization describes the lack of patient and family inclusion in decision-making, failure to use plain language and other health literacy strategies, and disregard for patient and family preferences. The author concludes that if the health care system is going to shift from paternalistic to patient- and family-centered, providers must be trained how to communicate and partner with patients and families. Even the most skilled health professionals, however, will not be able to deliver patient- and family-centered care if the system they work in is not designed to foster or support such care. Committed hospitals will integrate patient- and family-centered care throughout their organizations. This includes their mission statements, quality improvement activities, personnel policies, decision and self-management support, and patient portals. Payment policies can encourage, but are a blunt instrument to drive, health care toward patient and family-centered care. The author references resources to help hospitals make systematic changes to hard wire health literate and patient- and family-centered care.